DIGITAL RELIGIOUS COMMUNICATION IN AQIDAH AKHLAK LEARNING: FORMING STUDENTS’ RELIGIOUS ATTITUDES AT MI PLUS AL MAHMUD BLITAR - Arrinda Lutfiani Ayzzahro’; Muhammad Munir; Halimah; Ari Yansyah (LPPM IAD Probolinggo, 2026)
This study explores the integration of digital religious communication in Aqidah Akhlak learning to strengthen students’ religious attitudes at MI Plus Al Mahmud Blitar. The rapid growth of digital media has transformed teacher–student interactions in Islamic education, requiring pedagogical strategies that integrate technological innovation with value-oriented instruction. Employing a qualitative descriptive approach, data were collected through classroom observations, in-depth interviews, and documentation involving Aqidah Akhlak teachers and students engaged in digital-based learning. The findings reveal that digital religious communication serves as a transformative pedagogical medium that enhances student engagement, spiritual awareness, and moral understanding. Teachers utilize digital platforms such as interactive videos, online discussions, and digital storytelling to internalize Islamic values in ways that resonate with students’ digital lifestyles. The study concludes that integrating digital technology in Aqidah Akhlak learning is not merely a technical adaptation, but a form of spiritual pedagogical transformation that connects traditional Islamic values with contemporary digital contexts. These findings highlight the need for continuous teacher professional development in digital pedagogy to reinforce the effectiveness of Islamic education in the digital era.